ABC efflux transporters in brain vasculature of Alzheimer's subjects - Wijesuriya, Hasini C.; Bullock, Jocelyn Y.; Faull, Richard L.M.; Hladky, Stephen B.; Barrand, Margery A. (Brain research, 2010)
Multidrug efflux transporters of the ATP-Binding cassette (ABC) family, P-glycoprotein (Pgp), multidrug-resistance associated protein 4 (MRP4) and breast cancer resistance protein (BCRP), located on endothelial cells lining brain vasculature play important roles in limiting movement of substances into and enhancing their efflux from the brain. Signals from the surrounding brain normally maintain such barrier function but these may become altered in CNS pathologies such as Alzheimer's disease (AD). Previous studies have reported decreases in the glucose transporter, Glut-1, in brain vasculature of AD patients. The present study investigates the status of the multidrug efflux transporters. Sections of frozen brain from hippocampal region obtained from male AD and age-matched non-demented cases were examined for amyloid plaques and Dkk-1 expression and subjected to dual fluorescence immunochemical staining using antibodies against Pgp, BCRP or MRP4 and von Willebrand factor. Protein expression of each transporter was assessed using confocal microscopy, quantifying peak fluorescence values of cross sectional profiles across brain microvessels. Results in brain microvessels revealed expression of Pgp protein to be significantly lower in hippocampal vessels of patients with AD compared to normal individuals whereas that of MRP4 or BCRP protein was not. By contrast, analysis of the sections at protein level via Western blotting or at transcript level by qRT-PCR did not reveal significantly lower expression for either Pgp or BCRP. Such analysis did however reveal higher than normal expression in the AD brains of MRP4, probably due to gliosis, MRP4 being present also in glial cells. ► Do conditions in Alzheimer's brains affect efflux transporters on brain microvessels? ► Immunofluorescent staining for P-glycoprotein, BCRP or MRP4 in AD and normal brains. ► Transporter levels in brain microvessels quantified by confocal microscopy. ► Pgp but not BCRP or MRP4 was significantly lower in hippocampal vessels in AD cases. ► MRP4 at non-vascular sites correlated with increased glial cell number in AD brains.